AN EVALUATION OF IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL ON NATURAL SCIENCE LEARNING - Chusni, Muhammad Minan (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This study analyzes the quality of preparation, process, and learning outcomes in applying the discovery learning model. The method used in this research was evaluation with the Countenance Stake model. The population of this research was natural science students and teachers throughout Indonesia. The sample was the seventh-grade students from Sleman Regency and teachers representing several provinces. Data collection was through document review, observation sheets, and teacher and student questionnaires. Data were analyzed using qualitative descriptive technique. The results of this study indicated that the quality of the preparation and implementation process of the discovery learning model was quite good. Student learning outcomes were fairly good but had not applied assessments of critical skill, problem-solving, creativity, and innovation as a requirement of 21st-century learning evaluation. The study results were expected to provide an overview of the quality of teacher preparation, process, and learning outcomes in applying the discovery learning model. Abstrak: Penelitian ini bertujuan untuk menganalisis kualitas persiapan, proses, dan hasil belajar dalam menerapkan model discovery learning. Metode yang digunakan dalam penelitian ini adalah penelitian evaluasi dengan model Countenance Stake. Populasi penelitian ini adalah siswa dan guru IPA se-Indonesia dengan sample siswa berasal dari Kabupaten Sleman serta guru dari perwakilan beberapa provinsi. Pengumpulan data menggunakan lembar telaah dokumen, lembar observasi, angket guru, dan angket siswa. Data dianalisis dengan teknik deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa kualitas persiapan dan proses pelaksanaan model discovery learning sudah cukup baik. Hasil belajar siswa cukup baik, namun belum menerapkan penilaian keterampilan kritis, pemecahan masalah, kreativitas dan inovasi sebagai tuntutan dalam penilaian pembelajaran abad 21. Hasil penelitian diharapkan dapat memberikan gambaran umum tentang kualitas persiapan, proses, dan hasil belajar guru dalam menerapkan model discovery learning.